What's Left to Tax? Partisan Reallocation of Trade Taxation in Less Developed Countries. (September 2017) - Ha, Eunyoung; Rogers, Melissa
Trade liberalization has reduced trade tax revenue in most less developed countries (LDCs). The options to replace this tax, which has historically been LDCs' primary source of tax revenue, are limited by competitive pressures in the global economy. Using time-series error correction models, we assess how partisan politics shaped the reallocation of taxes in thirty-eight LDCs from 1975 to 2009. We argue that leftist governments have a vested interest in recovering lost revenue to fund spending that benefits their constituencies but they are highly constrained by the market signaling effects of increasing taxes. We find that leftist governments retained higher levels of falling tax revenue and offset trade tax losses with progressive personal income taxes (PITs). Nonetheless, leftist governments appeared reluctant to increase revenue from corporate income or social security taxes, which impose costs on business. To make up for the trade revenue loss, leftists instead relied more heavily on regressive consumption taxes, which are the most lucrative and market-friendly supplements to preferred PIT. Leftist parties in LDCs demonstrate redistributive concerns, but their tools and the lasting effects of their reforms are limited by strong market constraints.